Moses as Pharaoh’s Equal - Horns and All - Rendsburg, Gary A. (The Biblical archaeology review, 2023)
In the Spring 2023 issue of BAR, Lee M. Jefferson provided an excellent survey of how the horns of Moses (see Exodus 34:29-30, 35) were reinterpreted over the centuries in his article, "The Horns of Moses." Whereas earlier readers, including Jerome, who translated the Bible from Hebrew and Greek into Latin, understood the phrase "the […]